2007
DOI: 10.21236/ada473510
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Examination of a Hall Thruster Plume (Preprint)

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…There is evidence, however, that the presence of physical probes near regions of propellant ionization and acceleration can perturb the operation of the discharge [24]. So, optical diagnostics, including passive measurements like emission studies [25,26] and active measurements like laser-induced fluorescence (LIF) [11,12], are preferable for experimentally investigating breathing mode dynamics. Only recently have the requisite time-resolved optical diagnostics become available for a close, noninvasive examination of the interior of the discharge channel with high spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence, however, that the presence of physical probes near regions of propellant ionization and acceleration can perturb the operation of the discharge [24]. So, optical diagnostics, including passive measurements like emission studies [25,26] and active measurements like laser-induced fluorescence (LIF) [11,12], are preferable for experimentally investigating breathing mode dynamics. Only recently have the requisite time-resolved optical diagnostics become available for a close, noninvasive examination of the interior of the discharge channel with high spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Spacecraft interaction models have been developed which utilize near exit plane plasma information to estimate plume divergence and interactions with spacecraft surfaces. 1 A major limitation of these models is the accuracy of available near exit plane plume data for validation. The goal of this study is to characterize the near plume velocity field of a 600 W Hall thruster using excited state ionic xenon laser-induced fluorescence (LIF).…”
Section: Introductionmentioning
confidence: 99%
“…Past experimental measurements of the Hall thruster ion source beam indicated that the Debye length ranged from ϳ0.05 to ϳ1 mm throughout the plume from 8 to 20 channel centerline diameters downstream ͑CCDD͒ from the exit plane. 13 Thus, the 0.5 mm gap configuration is expected to be less than or equal to 10 Debye lengths for all locations studied with the nested Faraday probe. The 1.5 mm gap configuration is greater than 10 Debye lengths, and is oversized to highlight effects of a gap width greater than the 10 Debye length design criteria.…”
Section: B Nested Faraday Probementioning
confidence: 95%